The effectiveness of the regulation of goods and services procurement through the Electronic Procurement Service Information System (SILAPETRO) as an instrument of good university governance at Universitas Brawijaya - Shanti Riskawati; Zahwa Maulidina Afwija (Privietlab, 2026)
Universitas Brawijaya, a state university that previously operated as a Public Service Agency (Badan Layanan Umum), officially transformed into a Legal Entity State University (Perguruan Tinggi Negeri Berbadan Hukum, PTN-BH) in October 2021. This change in institutional status granted the university the autonomous authority to formulate and enact internal regulations, including those governing the procurement of goods and services. In exercising such authority, Universitas Brawijaya has enacted several Rector Regulations regulating the procurement of goods and services, inter alia, Rector Regulation of Universitas Brawijaya Number 98 of 2021 as amended by Rector Regulation Number 106 of 2022, as well as Rector Regulation Number 36 of 2022 concerning the Technical Guidelines for the Procurement of Goods/Services. Efforts to enhance the effectiveness and efficiency of goods and services procurement management have been pursued through the implementation of an electronic procurement system utilizing the Electronic Procurement Service Information System (Silapetro). Nevertheless, after nearly three years of implementation, various issues remain evident in terms of the regulatory framework and the practical execution of goods and services procurement at Universitas Brawijaya. Based on these circumstances, this study aims to examine and analyze the effectiveness of the regulation of goods and services procurement through Silapetro as an instrument for implementing the principles of Good University Governance at Universitas Brawijaya. This research employs a normative juridical method with a qualitative juridical approach, focusing on the analysis of primary legal materials, particularly Presidential Regulation Number 16 of 2018, as amended by Presidential Regulation Number 12 of 2021, as well as the relevant Rector Regulations governing goods and services procurement at Universitas Brawijaya.